Situation Report: Yugoslavia, 27 June 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Slovenian Communists Suggest Breaking Away from the League of Communists of Yugoslavia / by Milan Andrejevich Serbian Journalist Criticizes Milosevic / by Milan Andrejevich Milovan Djilas [Đilas] and Aleksandar Rankovic to Be Rehabilitated? Slovenia Offers Reconciliation with Serbia / by Milan Andrejevich Tension Escalates between Slovenia and Serbia / by Milan Andrejevich Youth Weekly Reports Maltreatment of an Ethnic Albanian / by Milan Andrejevich Ali Shukriu: Kosovo's Veteran Leader / by Louis Zanga